Migrant workers and class structure in Lebanon - Tabar, Paul (2014)
Whilst a few scholars have examined the situation of domestic workers, the issue of migrant labor as a whole (its contribution to the labor market, the status and situation of different categories of workers, and their impact on the resilience of the Lebanese social structure), is largely ignored, whereas the high proportion of foreign workers in Lebanon results in an increasing fragmentation of the working class, and the embeddedness of the Lebanese class structure in globalization. After examining the legal framework that organizes non-Lebanese workers in Lebanon, this paper discusses the findings of a field research on the labor force in the cleaning and the industrial sectors, by focusing on two case studies. Our research question addresses the social impact of the imbalance in the labor market between Lebanese and non-Lebanese workers, and the impact that such diversity (of both nationalities and class status) has on labor relations and the structure of the working class. Eventually, we argue that specific conditions of employment, characterised by the role of labor importing agencies, the so-called sponsorship system, outsourcing, the casualization of work and the ethnic fragmentation of the labor market, result in the segmentation of the labor force along national as well as gender lines. The strategy of many large employers in Lebanon appears to be based on the simultaneous and tactical application of inclusionary and exclusionary processes; i.e. the inclusion of migrant workers into the labor market whilst continuing to exclude them from available benefits as laid out in the Lebanese labor law.